World Development Report 1997 : The State in a Changing World - World Bank (New York: Oxford University Press, 2012)
This is the twentieth in the annual series assessing major development issues. The report is devoted to the role and effectiveness of the state: what it should do, how it should do it, and how it can improve in a rapidly changing world. Governments with both centrally-planned and mixed economies are shrinking their market role because of failed state interventions. This report takes an opposite stance: that state's role in the institutional environment underlying the economy, that is, its ability to enforce a rule of law to underpin transactions, is vital to making government contribute more effectively to development. It argues against reducing government to a minimalist state, explaining that development requires an effective state that plays a facilitator role in encouraging and complementing the activities of private businesses and individuals. The report presents a state reform framework strategy: First, focus the state's activities to match its capabilities; and second, look for ways to improve the state's capability by re-invigorating public institutions. Successful and unsuccessful examples of states and state reform provide illustrations.